Multi-antenna coded content delivery with caching: a low-complexity solution - Zhao,J; Mohammadi,Amiri M; Gunduz,D (IEEE Transactions on Wireless Communications, 2020)
We study downlink beamforming in a single-cellnetwork with a multi-antenna base station serving cache-enabledusers. Assuming a library of files with a common rate, we formulate the minimum transmit power with proactive caching andcoded delivery as a non-convex optimization problem. While thismultiple multicast problem can be efficiently solved by successiveconvex approximation (SCA), the complexity of the problemgrows exponentially with the number of subfiles delivered toeach user in each time slot, which itself grows exponentially withthe number of users. We introduce a low-complexity alternativethrough time-sharing that limits the number of subfiles receivedby a user in each time slot. We then consider the joint design ofbeamforming and content delivery with sparsity constraints tolimit the number of subfiles received by a user in each time slot.Numerical simulations show that the low-complexity scheme hasonly a small performance gap to that obtained by solving the jointproblem with sparsity constraints, and outperforms state-of-theart results at all signal-to-noise ratio (SNR) and rate values witha sufficient number of transmit antennas. A lower bound onthe achievable degrees-of-freedom (DoF) of the low-complexityscheme is derived to characterize its performance in the highSNR regime.